Stimulation of Erythrocyte Membrane Blebbing by Naproxen Sodium. Issue 1 (13th January 2020) - Ilyas, Sajida; Jilani, Kashif; Sikandar, Muhammad; Siddiq, Saba; Riaz, Muhammad; Naveed, Ayesha; Bibi, Ismat; Nawaz, Haq; Irfan, Muhammad; Asghar, Asma
Naproxen sodium is a nonsteroidal anti-inflammatory drug (NSAID) having antipyretic and analgesic properties, mainly used for the treatment of rheumatoid arthritis and osteoarthritis. Eryptosis is an alternative term used for suicidal erythrocyte death. In the current study, eryptotic effect of naproxen sodium characterized by membrane blebbing was investigated in erythrocytes after 48 hours of treatment with different concentrations (1-25 µM). The experimental work related to investigation of eryptosis was done by cell size measurement and confirmation of calcium role in the induction of membrane blebbing. As a possible mechanism of eryptosis, oxidative stress induced by naproxen sodium was determined by catalase, glutathione peroxidase, and superoxide dismutase activities. Similarly, hemolytic effect of naproxen sodium was also determined by hemolysis measurement. Results of our study illustrated that the therapeutic doses (10-25 µM) of naproxen sodium induce oxidative stress, confirmed by significant decrease in superoxide dismutase, catalase, and glutathione peroxidase activities that lead to the triggering of cell death by eryptosis and hemolysis.